Solvent-extracted soybean meal top-dressed on a fresh cow diet increased milk production, but not milk components, and decreased plasma non-esterified fatty acids - Mohammad Ghelichkhan; Hamid Amanlou; Ehsan Mahjoubi; Robert A. Patton (Czech Journal of Animal Science, 2019)
Post-ruminally infused casein has increased milk and milk protein yield in post-partum cows. We theorised top dressing (TD) higher amounts of soybean meal (SBM) might mimic these effects. Fifty-one multiparous Holstein cows 1 day after calving were assigned to 3 dietary treatments: a base total mixed ration (CON) with 196 g/kg crude protein and 329 g/kg neutral detergent fibre; 17 cows TD with l kg of SBM (SBM1); and 17 cows TD with 2 kg of SBM (SBM2) for 30 days. Milk and milk components were measured at days 9, 18, and 27. Rumen and urine samples were collected on day 27; blood samples were obtained on day 30. Statistical inference was by JMP software (Version 10.0.2, 2012) with production variables analysed as a repeated measures design. Cows fed SBM increased milk yield (P = 0.02; 35.4, 36.6, and 42.6 kg/day for CON, SBM1, and SBM2, respectively). Yield of milk true protein was not different among treatments. Cows fed SBM had lower serum non esterified fatty acids concentrations at day 30 (1.35, 1.13, and 0.59 mM/l; P < 0.01). We conclude that SBM TD beginning immediately after calving may increase milk yield rapidly and decrease dependence on fatty acids for energy.